Cough and airway disease: the role of ion channels - Bonvini,SJ; Belvisi,MG (Pulmonary Pharmacology and Therapeutics, 2017)
Cough is the most common reason for patients to visit a primary care physician, yet it remains an unmet medical need. It can be idiopathic in nature but can also be a troublesome symptom across chronic lung diseases such as asthma, COPD and idiopathic pulmonary fibrosis (IPF). Chronic cough affects up to 12% of the population and yet there are no safe and effective therapies. The cough reflex is regulated by vagal, sensory afferent nerves which innervate the airway. The Transient Receptor Potential (TRP) family of ion channels are expressed on sensory nerve terminals, and when activated can evoke cough. This review focuses on the role of 4 TRP channels; TRP Vannilloid 1 (TRPV1), TRP Ankyrin 1 (TRPA1), TRP Vannilloid 4 (TRPV4) and TRP Melastatin 8 (TRPM8) and the purinergic P2X3 receptor and their possible role in chronic cough. We conclude that these ion channels, given their expression profile and their role in the activation of sensory afferents and the cough reflex, may represent excellent therapeutic targets for the treatment of respiratory symptoms in chronic lung disease.